Amyand's hernia in a 5-year-old child: a case report and literature review. Issue 9 (9th September 2020) - Khanal, Bhawani; Agrawal, Sunit; Gurung, Roshan; Sah, Suresh; Gupta, Rakesh Kumar
Abstract: Amyand's hernia in a child is a very rare entity. It poses a diagnostic challenge to the surgeon due to its variety of presentation. We are presenting a case of a 5-year-old child who presented to our institute with right-sided irreducible inguinal hernia. On exploration, the content of the hernia was caecum with normal appendix for which herniotomy with appendectomy was done.